potrzebuję tego jak najszybciej, plisss

Odpowiedź:
zad1
f(x)=-2x²+7x-4 a=-2 b=7 c=-4
f(x)=1/5 x²-2x-1 a=1/5 b=-2 c=-1
f(x)=-3x+4x a=-3 b=4 c=0
f(x)=-x²+1 a=-1 b=0 c=1
zad2
A p=2 q=2 a>0
B p=-3 q=-3 a<0
C p=6 q=0 a>0
D p=0 q=-2 a<0
zad3
f(x)=-3(x-3)(x+1) x=2 f(2)=-3(2-3)(2+1)=-3*(-1)*3=9
f(x)=[tex]\frac{1}{2}( x-2)^2-1[/tex] x=-3
f(-3)=[tex]\frac{1}{2} (-3-2)^2-1=\frac{1}{2} *25-1=12\frac{1}{2} -1=11\frac{1}{2}[/tex]
f(x)=x²+x+ 3/2 x=1/2
f(1/2)=[tex](\frac{1}{2} )^2+\frac{1}{2} +\frac{3}{2}=\frac{1}{4} +2=2\frac{1}{4}[/tex]
Szczegółowe wyjaśnienie: